Pengaruh Profitabilitas, Likuiditas, Leverage, Growth Opportunities, Expected Dividend Dan Total Asset Turn Over Terhadap Kebijakan Dividen Studi empiris pada perusahaan manufaktur, pertanian, kehutanan, perikanan, pakan ternak dan peternakan pada tahun 2011-2014 - Supriyanto, Dr. Triyono, M.Si (2016)
This research aims to analyze and abtain empirical evidence about the effecs of profitability, liquidity, leverage, growth, expected dividend, and total asset turn over to dividend policy. The research population was manufacturing companies, agriculture, forestry and fishing, animal feed and husbandry listed in Indonesian Stock Exchange (IDX) in period of 2011-2014. The Sample are collected by purposive sampling method, and collected of 36 studies . Analysis method of this research used multiple linier regresion. The result showed that liquidity, expected dividend, and total asset turn over did not significantly effect to dividend policy. The profitability and leverage has negatively effect to dividend policy and growth has a positive effect to dividen policy.